Kerjasama Institusi Pendidikan Tinggi Dan Pemerintah Daerah Dalam Mengatasi Kenakalan Remaja Di Sekolah - Arcanita, Rapia; Putrajaya, Guntur (BELAJEA: Jurnal Pendidikan Islam, 2019)
This research was done based on  1) increasing a number of juvenile in detention class II a Curup. 2) there was a wish of regional government  to realize religius and good character education. 3) most of IAIN Curup students? background are from public school including senior high school in Rejang Lebong regency.  Based on those considerations, therefore the researcher tried to reveal how werethe form and model implementation of the shared concept like in the field. The subject of this research are some senior high schools  in Rejang Lebong regency using purposive sampling model of Sugiono. From the answer of respondents knowing that religius and character education in senior high school in Rejang Lebong regency had been realized however had not been maximal. It happened because some barrier factors, both from the school (internal) and outside school (external) as described on the first session. Then, the cooperation of higher education (IAIN) and regional government to resolve juvenile delinquency in school had not been maximal actually, because  it had not touched the school specifically, it was done only daily routine, such as PPL, KPM,  or Friday safari. But, the school desire for IAIN Curup as coach in religious spiritual progress had not been achieved